Results of Bronchoscopic Lung Volume Reduction with One-way Valve in Patients with Severe Emphysema in Vietnam - Ta Ba T; Dong Khac H; Do Q; Dao Ngoc B; Nguyen Huy L; Nguyen Viet N (Journal of Respiratory Diseases, 2018)
Background Bronchoscopic lung volume reduction (BLVR) has been applied in COPD patients with heterogeneous emphysema. In this first clinical trial in Vietnam, we evaluated the safety and initial results of BLVR by one-way valve in COPD patients with severe emphysema. Methods We performed a prospective, nonrandomized, single center longitudinal study in 30 stable COPD patients with heterogeneous severe emphysema on CT-scanner, the average age of 65.17 years old, FEV1≤35 %pred., TLC ≥ 100 %pred., RV ≥ 150 %pred. and 6MWT < 450 meters. The Zephyr one-way bronchial valves (PulmonX, Redwood City, CA, USA) with the size of 5.5 mm and 4mm were placed in lobar or segmental bronchi via flexible bronchoscopy. 28 patients were placed only one valve, 1 patient with two and 1 patient with three valves. 23 valves with the size 5.5 mm diameters and 10 valves with the size 4.0mm used. All patients received optimal medical treatment at the time of procedure and during the study period. Outcomes will be assessed at 3 months after treatment include the changes of clinic, and lung function, the occurrence of complications. Results After 3 months, mean CAT scores decreased significantly compared with before procedure (17.73 ± 3.53 vs 20.10 ± 3.58) (p<0.05), with the median change of 2.73 points and the improvement more than 2 points in 76.67% of patients. 6 MWT increased at 3 months with mean 32.13 meters, 93.33% of the patients increased 6MWT, 46.67% of the patients increased 6MWT more than 26 meters. MRC decreased with the median change of 0.5 score. VC decreased by a mean 0.2 (L) (0.42 - 0.02), FEV1 increased by a mean 0.05 (L) (0.04 - 0.05) but not statistically significant (p>0.05); FVC increased by a mean 0.14 (L) (0.01 - 0.28), RV decreased by a mean 0.62 (L) (1.05 - 0.2), TLC decreased by a mean 0.52 (L) (0.77- 2.4) with statistically significant (P<0.05). The early complications were 13.33%, the later complications were 23.34% of the patients. Conclusions The unilateral bronchoscopic lung volume reduction with one-way valve (mainly one valve) in treatment of heterogeneous severe emphysema in stable COPD patients in Viet Nam have shown that this procedure is safe with encouraging initial results.
Keywords: Chronic obstructive pulmonary disease